Identification and expression analysis of c-type and g-type lysozymes genes after Aeromonas hydrophila infection in African catfish - Hasan Nasrullah; Yanti Inneke Nababan; Dwi Hany Yanti; Dian Hardiantho; Sri Nuryati; Muhammad Zairin Junior; Julie Ekasari; Alimuddin Alimuddin (Jurnal Akuakultur Indonesia)
ABSTRACT